Decision Support System for Assessing Community Satisfaction with Sari Mutiara Lubuk Pakam Hospital Services Using the Oreste Method - Bella Puspa Dewi; Dedi Candro Parulian Sinaga (Putaka Timur Publisher, 2021)
Sari Mutiara Hospital is one of the health care hospitals in the Lubuk Pakam City area. Many people come and go every day. Of course, people have various responses to the Sari Mutiara Hospital services, some are satisfied and some are not. For this reason, a system is needed to determine the level of community satisfaction with the Sari Mutiara hospital. To improve the services of Sari Mutiara Hospital to the community. The solution to the problems mentioned above is to build a decision support system to assist in determining community satisfaction with Sari Mutiara Hospital. The method chosen to support the above problem solving is the Oreste method.